Inflammatory and Hemostatic Response to Cardiopulmonary Bypass in Pediatric Population: Feasibility of Seriological Testing of Multiple Biomarkers - (:unkn) unknown (WILEY-BLACKWELL, 2010)
Perioperative myocardial and cerebral damages are the major determinants of postoperative morbidity and mortality in pediatric cardiac surgery. Cardiopulmonary bypass (CPB) causes alterations in the levels of biomarkers related to inflammation, tissue damage, and other tissue pathologies. Early and accurate evaluation of inflammation and tissue damage would therefore be clinically useful. Our objective is to assess the suitability of using Multi-Analyte Profiling (MAP) (Rules Based Medicine, Austin, TX, USA) in pediatric cardiac surgery as a potential surrogate marker of clinical outcome. MAP technology platform allowed us to analyze 90 different biomarkers using only 100 mu L of plasma to detect any changes in the levels of 90 biomarkers. Plasma samples (100 mL) were collected at five different time points: 1. before midline incision; 2. on CPB for 3-5 min; 3. at the end of CPB; 4. 1 h after CPB; and 5. 24 h after CPB. After removing the outliers, the average and standard deviation of the values obtained from the 10 patients were calculated for each time point. The average values of each biomarker at each time point were then compared to each other and to the baseline. The pilot protocol included 10 patients (ages from 3 months to 4 years old) with similar Jenkins risks stratifications who underwent nonpulsatile CPB. We detected changes in the levels of 90 biomarkers. Biomarkers were assessed in groups. Myeloperoxidase (MPO) and pregnancy-associated plasma protein A (PAPP-A) were the earliest markers to rise with 49- and 18-fold increases 3-5 min after the onset of CPB, respectively. The most striking increase was noted in the heart-type fatty acid-binding protein (FABP) levels. FABP increased 25, 193, 151, and 4-fold at time points 2, 3, 4, and 5, respectively. Surges in the novel markers of injury were followed by the markers of inflammation (i.e., C-reactive protein, interleukins) peaking at 24 h after CPB. This pilot study shows that it is possible to measure 90 different biomarkers using only a very small sample of plasma to evaluate the effects of CPB. Novel markers of tissue injury (FABP, PAPP-A, or MPO) are the earliest markers to rise. Serial monitoring of multiple biomarkers may help to predict and improve outcomes after pediatric cardiac surgery.
Keywords: Pediatric cardiopulmonary bypass; Biomarkers; Multianalyte profiling; MYOCARDIAL DAMAGE; CARDIAC-SURGERY; PROTEIN